2016
DOI: 10.1044/2015_jslhr-h-15-0098
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Nature of Hearing Loss in 22q11.2 Deletion Syndrome

Abstract: Hearing loss in 22q11.2 deletion syndrome is highly prevalent and both conductive and high-frequency sensorineural in nature. The age-dependent absence of DPOAEs in 22q11.2 deletion syndrome suggests cochlear damage underlying the high-frequency hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…They furthermore estimated that less than 2.2% of children in this age group had sensorineural hearing loss, and less than 3.5% of children between three and 19 years had conductive hearing loss . Although the outcome of our included studies differed much, 20 of 21 studies found a prevalence of hearing loss greater than the previously reported 14.9% hearing loss in the general population …”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…They furthermore estimated that less than 2.2% of children in this age group had sensorineural hearing loss, and less than 3.5% of children between three and 19 years had conductive hearing loss . Although the outcome of our included studies differed much, 20 of 21 studies found a prevalence of hearing loss greater than the previously reported 14.9% hearing loss in the general population …”
Section: Discussionmentioning
confidence: 68%
“…Rates of hearing loss, all types of hearing loss included, varied from 6.0% to 60.3%. Aside from decreased hearing thresholds in standard frequencies, Van Eynde et al and Zarchi et al found hearing loss to be more present and more severe in the high tones (Van Eynde et al measured thresholds at 4, 8, 9, 10 and 11.2 kHz and Zarchi et al at (4), 6 and 8 kHz). Conductive hearing loss was most prevalent in most studies (range 5.6% to 53%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been extensively documented that hearing loss is more frequent in children with trisomy 21 than in healthy children . Research has shown that 50–90% of children with trisomy 21 will have at least a mild to moderate hearing loss compared with 0.25–1% in healthy children .…”
mentioning
confidence: 99%